Challenging the orthodoxy on pupil gang involvement: When two social fields collide. (7th June 2018) - Irwin‐Rogers, Keir; Harding, Simon
Abstract : Based on fieldwork conducted in five alternative provision schools across three large cities in England, this article explores the relationship between young people's involvement in urban street gangs and their attitudes and behaviour in school. By applying and developing a lens of social field theory, the article highlights the ways in which gang‐involved young people navigate their way between two distinct social fields, namely that of the street gang and that of the school. Although pupil gang involvement can raise significant issues for schools, particularly around violence and educational engagement, our findings challenge the prevailing orthodoxy that depicts an entirely negative portrait of the effects of gang involvement on pupils' attitudes and behaviour. Instead, through an analysis of interview and observational data, we argue that there is nothing inevitable about the internal logic of a gang social field permeating a school's gates. Young people involved in gangs do not typically spend their entire waking hours wedded to a 'gang member' identity—if they are given the opportunity to transition away from the gang social field when they enter the school gates, they will often embrace it. In short, the links between pupils' involvement in gangs, violent behaviour in school and engagement in education are more contingent and nuanced than is suggested by the literature on gangs and schools to date.